Analysis and Design of the Web Base Guesthouse Reservation Information System at Universitas Terbuka Using The Prototype Method - Kusyadi, Irpan; Junianto, Mochamad Bagoes Satria; Basri, Hasan (Department of Informatics Engineering, 2025)
Efficient guesthouse reservation management is crucial to supporting the accommodation services provided by Universitas Terbuka. Currently, the existing system faces limitations in data management and time efficiency, particularly in the reservation, recording, and reporting processes. This study aims to analyze and design a web-based guesthouse reservation information system that is expected to facilitate the reservation process more effectively and transparently. The design approach used is the prototype method, which allows system development based on early user feedback. The research begins with identifying requirements through the stages of communication, planning, modeling, prototyping, and feedback collection. The results of this analysis are then used as the basis for designing the system model and the initial user interface (UI/UX). The system prototype is then developed and iteratively evaluated by involving potential users, including guesthouse managers and prospective guests, to ensure that the final design meets user needs